Science fiction and the medical humanities. Issue 4 (24th November 2016) - Miller, Gavin; McFarlane, Anna
Abstract : Research on science fiction within the medical humanities should articulate interpretative frameworks that do justice to medical themes within the genre. This means challenging modes of reading that encourage unduly narrow accounts of science fiction. Admittedly, science studies has moved away from reading science fiction as a variety of scientific popularisation and instead understands science fiction as an intervention in the technoscientific imaginary that calls for investment in particular scientific enterprises, including various biomedical technologies. However, this mode of reading neglects science fiction's critical relationship to the construction of 'the future' in the present: the ways in which science fiction proposes concrete alternatives to hegemonic narratives of medical progress and fosters critical self-awareness of the contingent activity which gives 'the future' substance in the here-and-now. Moreover, the future orientation of science fiction should not distract from the function of medical science fiction as 'cognitive estrangement': the technological innovations that dominate science-fiction narratives are less concrete predictions and more generic devices that explain in historical time the origins of a marvellous world bearing provocative correspondences to our own, everyday reality. The editorial concludes with a series of introductions to the articles comprising the special issue, covering the print edition and a special online-only section.